Penyelesaian Perkara Pelanggaran Hak atas Merek - I Gede Mahendra Juliana Adiputra; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2020)
The existence of competition causes the original brand owner to feel disadvantaged because the sales result has decreased. It is permissible for someone to use another party's mark as long as they ask permission from the trademark owner first. The owner can give trademark rights to other people as agreed in an agreement. The formulation of the problem in this research is as follows: how is the legal protection of trademark rights and how to resolve violations of trademark rights. The research method used in this research is normative legal research. The results of the discussion in this study are as follows: Legal protection of the right to a trademark has been regulated by Law Number 20 of 2016 concerning Trademarks and Geographical Indications, in the provisions of the Law it is expressly stated that if it has been registered in the law that the right to a trademark has been protected. The sanction imposed on the perpetrator of the crime of trademark rights is a fine of Rp. 20,000,000, - (twenty million rupiah) on condition that if the fine is not paid, he will be subject to imprisonment for 6 (six) months. Settlement of trademark cases can be carried out through institutions that can be used to resolve trademark disputes, including: Alternative Dispute Resolution, Arbitration and Courts. Alternative dispute resolution wants the disputing parties to resolve their own dispute with the aim of obtaining a mutual agreement, if the agreement fails, can take arbitration, namely the disputing parties to be able to resolve the dispute to the arbitration institution based on the agreement, furthermore, if the arbitration is successful the last action is through the court, namely the commercial court which has the authority to adjudicate trademark disputes.